Biofuel Programme and Dissemination of Research Data through World Wide Web: Indian Scenario - ., Ajit; Jabeen, Nighat; Handa, A.K.; Kumar, R.V.; ., Uma (Indian Journal of Agroforestry, 2020)
India ranks sixth in terms of energy demand, accounting for 3.6% of total global energy demand. While its energy demand is expected to grow at 4.8% annually. The energy demand of the country in totality and specifically pertaining to the transport sector cannot be met by fossil fuels. Moreover, the ever-increasing petroleum prices day by day have compelled us to search for alternatives. Biomass energy in general and biofuels in particular are the potential substitutes to be tapped. As India is deficient in edible oils, non-edible oil is the main choice for producing biodiesel. Among the non edible oil-bearing trees, Jatropha (Jatropha curcas), Karanja (Pongamia pinnata), Mahua (Madhuca indica), Kokum (GarciniaÂ indica), Sal (Shorea robusta), Neem (Azadirachta indica), Kusum (Schleichera oleosa), Khakan (Salvadora oleidos and S. persica) has large economic potential. A study was initiated at NRCAF, Jhansi under the world bank funded INARIS project to compile all the published research articles/reports on biofuel species like Jatropha, Pongamia, Madhuca,Â Garcinia in the form of online bibliographic data bases so that it is easily accessible to researchers, planners, policy makers, etc. As on date, three important biofuel species namely Jatropha, Pongamia and Madhuca has already been to the cart of databases on agroforestry. Efforts are being made to add more and more biofuel species to this database. In Pongamia database, a total of 715 published Indian research record could be traced covering the three species of Pongamia in all during 1971 to the first quarter of 2006. The analysis revealed that maximum research has been carried out on pesticidal lines of Pongamia in India followed by disease & pests (52), manure and fertilizers (44), and land reclamation and restoration (41). Similarly in Jatropha database a total of 123 records have been appended covering the nine species of Jatropha between 1974-2005 with 25 records from pesticidal properties followed by genetic improvement (16), chemical composition consisting 14 records, medicinal value (12), disease & pests (8). Like wise in Madhuca database a total of 294 Indian Madhuca research records in all from 1971 to 2006 have been added covering the four species of Madhuca with 119 records followed by chemical composition consisting of 16 records, growth and yield (15). Besides tracing the bibliographic details of these records (including abstracts, location of study, year of publication, authors etc) one can also search records on other research categories pre designed in the database like disease and pests, manure and fertilizers, land reclamation and restoration, genetic improvement etc. These bibliographic research database has been hosted at the server of Indian Agricultural Statistics Research Institute (IASRI), New Delhi and these dynamic web pages are fully functional and one can visit at URL http://mirror.inaris.gen.in/net. to view, browse and download information on the subject.